Microneedle Drug Delivery Systems: Recent Advances, Clinical Applications, and Future Directions - Salman, Ahmed H.; Hasan, Ali Khalaf; Abbood, Mohammed Khalid (American Journal of Biomedicine and Pharmacy, 2025)
Microneedle (MN)-based drug delivery presents an innovative technology for minimally invasive and painless transdermal/ intradermal drug administration with a various combination of drugs. This review systematically compiles recent (2021–2025) findings in the field of fabrication methods, material developments, delivery systems, clinical translations, and commercialization. There are still challenges despite the rapid progress in large-scale manufacturing, biological stability and regulatory harmonization. Highlights amongst new developments are smart MNs combining with biosensors for feedback-controlled release, combination MNs for multi-agent therapy and AI guided design optimization. Resolution of these issues will facilitate more widespread clinical translation, personalized therapy and worldwide control. The review ends with a summary of the major opportunities and research areas in next generation microneedle technologies.